PENGARUH SUHU TERHADAP MODULUS ELASTISITAS DAN ANGKA POISSON BETON ASPAL LAPIS AUS (AC-WC) DENGAN KAPUR SEBAGAI FILLER - Wiyono, Arselina Wood Ward; Setiawan, Arief; Nurhidayat, Nurhidayat (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2012)
Today the use filler in asphalt concrete mixes such as AC-WC has done much to improve durability. hydrated lime is the only one.The purpose of this reasearch was to determine theeffect of temperature variation of the modulus of elasticity and Poisson ratio figures asphalt contred wearing course (AC-WC) using hydrated lime as a filler. Variations hydrated lime used inthis reasearch is a variation of the levels of hydrated lime: dust filer 0%, 25% and 50%, and the temperature variation is 20°C, 30°C, 40°C, 50°C, 60°C. The results showed that the higher the test temperature, the diminishing value of modulus of elasticity, but inversely proportional to the number poisson where the higher the test temperature, the higher the number poissonnya, causing the mixture to become more flexible when the load is given. The results showed that the greater the level of lime, the diminishing value of modulus of elasticity, but inversely proportional to the number poisson where greater levels of calcium, the higher the number poissonnya, causing the mixture to become more flexible when the load is given.Keyword:  Temperature, Asphalt Concrete wearing course, HydratedLime, Indirect Tensile Strength (IDT-Strength), Modulus of Elasticity, Poisson ratio.